MRI assisted focal boost integrated with HDR monotherapy study in low and intermediate risk prostate cancer (MARS): Results from a phase II clinical trial. (December 2019) - Alayed, Yasir; D'Alimonte, Laura; Helou, Joelle; Ravi, Ananth; Morton, Gerard; Chung, Hans T.; Haider, Masoom; McGuffin, Merrylee; Zhang, Liying; Loblaw, Andrew
Highlights: MARS is a phase II trial of 19 Gy HDR monotherapy with MRI-guided focal boost. Sixty patients were enrolled, the majority had intermediate risk prostate cancer. No acute or late grade ≥3 bowel or urinary toxicity was observed. The cumulative BF probability was 15.2% at 36 months and 31.6% at 48 months. Focal boost to the MRI-specified lesion did not adequately improve local control. Abstract: Purpose: There is growing concern that single-fraction HDR monotherapy to a dose of 19 Gy is suboptimal for the treatment of localized prostate cancer. We report the results of a phase II prospective trial of single-fraction 19 Gy HDR monotherapy with MRI-guided simultaneous focal boost. Methods: Eligible patients had low or intermediate risk prostate cancer and an identified lesion on MRI. TRUS based single-fraction HDR monotherapy with MRI fusion was delivered. The dose prescribed was 19 Gy to the prostate and ≥23 Gy to the dominant intraprostatic lesion (DIL). ADT was not used. The purpose is to report early efficacy results. Results: 60 patients were enrolled, with a median follow-up of 39 months. With MRI T-stage incorporated into the risk-group criteria, 8% had low-risk, 35% had favorable intermediate-risk and 57% had unfavorable intermediate-risk disease. The median dose to 90% of the DIL (D90) was 27.2 Gy, and the median prostate V100% was 96.9%. No acute or late grade ≥3 bowel or urinary toxicity was observed. The cumulative BF probability was 15.2% at 36 months and 31.6% at 48 months. All patients that were fully investigated had local failure only, and 88% of the local failures were at the site of original DIL. The median PSA nadir was 0.79 ng/ml, with a median time to nadir of 32 months. Conclusions: Focal boost to the MRI-specified gross tumor was well tolerated, but did not adequately improve local control. Single-fraction HDR monotherapy to 19 Gy for prostate cancer provides suboptimal local control, and should not be offered outside of clinical trials.